Experiments involving second order effects in high-intensity, high-frequency acoustic fields - Wanklyn, Kevin Michael (Kansas State University, 2011)
Cavitation is a long studied phenomenon, fascinating and varied. Observed cavitation thresholds vary, typically ranging from the vapor pressure of the liquid to several atmospheres. Recent studies in cavitation involving very clean liquids give rise to thresholds that surpass 100 atmospheres. Calibrating such high intensity, high frequency, focused acoustic fields presents a significant challenge. The present investigation describes how it is possible to exploit the second order acoustic effect of radiation pressure to seek reliable calibration of the high intensity acoustic fields. Experiments describe how to account for the attendant second order effect of acoustic streaming in the evaluation of the radiation force to accomplish meaningful calibration. Beyond the measurement of the second order quantities associated with cavitation, the work also presents a first investigation of a direct estimation of implosion energies of collapsing bubbles near well-characterized surfaces.
Keywords: Acoustics; Second order effects; Mechanical Engineering (0548)